As siglas da igreja de Boelhe - Guedes, César (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2019)
In this essay we seek to analyse the masons’ marks from the church of S. Gens de Boelhe and answer some questions related to the construction of the monument and its builders. The systematic analysis of a building´s mason marks can provide informations related with the number of masons that worked in a particular building and the stages and rhythms of its construction. A systematic gliptographic survey may also allow to foresee regional or national movement of groups of masons.